Organic Synthesis on solid Phase : - Dorwald, Florencio Zaragoza (Wiley-VCH, 2002)
This is the number-one successful book on solid phase organic synthesis, now in its second, expanded edition. It offers the reader · a comprehensive overview of supports, spacers, and linkers · 15% more contents · everything there is to know about reactions and their applications · clear structure · numerous experimental guidelines for use in practice The ideal reference for newcomers and experts. "... I have no doubts that this text will be the benchmark for future publications on the subject, and a very hard act to follow for authors planning books of their own on this red hot topic." The Alchemist